ANALISA PERHITUNGAN BEBAN PENDINGINAN RUANG PERANGKAT INTERNET DI PT. X - SITE KEDATON - WINARNO, SUKO (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2019)
Abstract -- The cooling process in the internet device room has an important function in maintaining room temperature so that the equipments in the room stay at the desired temperature. With optimal cooling, the equipments in the room are expected to function optimally. The author analyzes the condition of the internet device room with the research method used is by taking field data and analyzing the calculation of the data using formula formulas obtained from the literature. After calculating the data , then the average value of the Thermal load of the room is 3260 Watt,  the average of room temperature is 22.95 0 C, the average enthalpy value in the room is 42.72 kJ / kg.a. Then the enthalpy value of the evaporator is 35.86 kJ / kg.a. Then the average value of the mass flow rate coming out of the evaporator is 0.48 Kg / s. From these calculations it can be concluded that the highest room temperature is at 11.00 AM, the average room thermal load value is at 1.20 PM, then the highest enthalpy value of the room occurs at 11.00 AM, then the highest value of enthalpy of the evaporator occurs at 11.00 AM, and the highest average value of mass flow rate occurs at 1.20 PM.